PENGELOLAAN DAN PENYELENGGARAAN PERPARKIRAN DI KAWASAN PASAR AUR KUNING KOTA BUKITTINGGI TAHUN 2024 - Jayanti, Nelvita Isra; Febrina, Rury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Aur Kuning Market is a strategic economic center in Bukittinggi City, which is crowded daily by vehicles of visitors, traders, and the general public. This condition demands optimal parking management and services to support smooth traffic flow and increase local revenue through parking retributions. This study aims to analyze the management and organization of parking in the area in 2024 using a descriptive qualitative approach, guided by the theories of Good Governance, Public Service, and Parking Regulation. The findings reveal that formal parking management has only been implemented at the Aur Kuning Terminal with contracted parking attendants and tariff application based on Regional Regulation Number 3 of 2010, while five other locations are still operated by informal attendants without full supervision from the local government. Limited human resources, insufficient budget, and low public awareness of parking regulations are the main obstacles that hinder the optimal implementation of good governance principles. Kata Kunci: Bukittinggi, Pasar Aur Kuning, Pelayanan Publik, Pengelolaan Perparkiran, Retribusi Parkir, Tata Kelola Pemerintahan